TANGGUNG JAWAB DIREKSI TERHADAP AKTIVITAS PERSEROAN TERBATAS YANG BELUM BERSTATUS BADAN HUKUM - Esa Septianingrum Semara, A. A. Istri; Dewi Kasih, Desak Putu; Purwanti, Ni Putu (Kertha Semaya : Journal Ilmu Hukum, 2015)
This paper discusses the responbility of the directors on the activities ofthe limitied liability company that is not yet legal status. This paper aims toidentify and analyze the legal consequences and responsibilities of the managingdirectors who have limitied liability legal status. Types of research in this study,using the normative nature of the research descriptive. This paper presented astudy that from a limitied liability legal status, then since that time the law treatsshareholders and directors apart from the limitied liability company itself. Thusshareholders who do not have an interest in a limitied liability company wealth,also not responsible for the debts of the company.
Keywords: Corporation, Responsibility, Limited Company